Uncovering Long Term Relationships between Oil Prices and the Economy: A Time-Varying Cointegration Analysis - Fabian Gogolin; Fearghal Kearney; Brian M. Lucey; Maurice Peat; Samuel Vigne (Queen's University Belfast, Queen's Management School, 2018)
Establishing the relation between oil price movements and macroeconomic performance is of great importance for firms and policymakers, alike. Prior studies established this relation using the assumption that the long-run relation is intertemporally constant. However, there is much recent evidence demonstrating that this assumption may not hold in practice. To address this issue and go beyond the restrictive time-invariant environment, we employ the use of the time-varying cointegration framework of Bierens 2010. We present evidence of the long-run oil-economy relation evolving over the 1974-2015 period, with major events such as the Gulf War and the financialisation of commodity markets proving to be driving forces across the U.S., European and G7 economies considered.
Keywords: Q43; 330; Marcoeconomy; oil prices; WTI Oil; Brent Oil; long-run